(untitled) (International Journal of Food and Nutritional Sciences, 2022)
It was in the beginning of the 16th century that the first seeds of British imperialist ideologies were sown. Queen Elizabeth I played an important role in the British Empire setting its eyes on lands far off and unknown. This was done with the intention of spreading the wings of British rule far and wide. The British troops sailed off to many lands hitherto unknown to them. Eventually, it was only a matter of time before the British claimed many foreign lands as their own and wielded their imperial power over them. C. S. Lewis (29 November 1898 – 22 November 1963) was a British writer famed for his children’s fiction. Lewis’s The Chronicles of Narnia: The Voyage of the Dawn Treader tells the tale of the journey of a king and his companions into unknown lands. As they enter new territories, they exercise their enormous power leaving an indelible imprint of their authority over these lands. Lewis fought alongside the British troops during World War I and thus was part of espousing the ambitious ideologies of British imperialism. This propagandist attitude can often be seen displayed in his works. This paper is an attempt to show how predilection for imperialist ambition and power clearly manifests itself in C. S. Lewis’s The Chronicles of Narnia: The Voyage of the Dawn Treader.